Smartphone use and musculoskeletal symptoms in nursing students - Taipe Toainga, Nathaly Anahi; Analuisa Jiménez, Eulalia Isabel (Enfermería Cuidándote, 2026)
Introduction: The use of smartphones has increased, becoming an essential tool for various activities, ranging from academic to recreational; however, their excessive use can have adverse health consequences, especially on the musculoskeletal system.Objective: To analyze the relationship between smartphone use and the presence of musculoskeletal symptoms in nursing students at the Technical University of Ambato.Methodology: A quantitative methodology was used, with a cross-sectional observational design and correlational scope. Two validated instruments were applied: the Smartphone Addiction Scale (SASV-SV) and the Nordic Musculoskeletal Symptom Questionnaire. The sample consisted of 242 students.Results: A positive correlation (0.001 < 0.05), albeit weak (0.335), was identified between smartphone use and the onset of musculoskeletal disorders in the previous 12 months. Likewise, a positive correlation of 0.001 < 0.05, also weak (0.208), was observed between smartphone use and the inability to perform normal activities due to musculoskeletal discomfort experienced in the past 12 months. However, there was no correlation between smartphone use and the onset of symptoms in the past 7 days.Conclusions: Prolonged smartphone use is correlated with musculoskeletal problems, underscoring the need to increase awareness about responsible smartphone use and reduce addictive use to mitigate adverse effects on student health.
Keywords: Musculoskeletal Diseases; Nursing Students; Smartphone; Technology Addiction